2017
DOI: 10.1097/fpc.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Genetic coding variants in the niacin receptor, hydroxyl–carboxylic acid receptor 2, and response to niacin therapy

Abstract: Objectives Niacin has been used for seven decades to modulate plasma lipids, but its mechanism of action is still unclear. We sought to determine whether variants in the niacin receptor gene, hydroxycarboxylic receptor 2 (HCAR2) are associated with lipid response to treatment. Methods Coding variants, rs7314976 (p.R311C) and rs2454727 (p.M317I), were genotyped in 2067 participants from the Atherothrombosis Intervention in Metabolic Syndrome with Low HDL/High Triglycerides and Impact on Global Health Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The characteristics of included studies are shown in Table 1. Among 42 eligible studies, 14 studies intervened with prebiotics (24, 29-39, 46, 47), 10 with probiotics (40,41,43,(48)(49)(50)(51)(52)(53)(54), 6 with synbiotics (24,44,(55)(56)(57)(58), 10 with microbial metabolites (27,28,(59)(60)(61)(62)(63)(64)(65)(66), and the remaining 4 with fecal microbiota transplantation (FMT) (24,25,45,67). Among these studies, 24) not only explored the respective but also the synergetic efficiency of FMT and the prebiotics on MetS.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The characteristics of included studies are shown in Table 1. Among 42 eligible studies, 14 studies intervened with prebiotics (24, 29-39, 46, 47), 10 with probiotics (40,41,43,(48)(49)(50)(51)(52)(53)(54), 6 with synbiotics (24,44,(55)(56)(57)(58), 10 with microbial metabolites (27,28,(59)(60)(61)(62)(63)(64)(65)(66), and the remaining 4 with fecal microbiota transplantation (FMT) (24,25,45,67). Among these studies, 24) not only explored the respective but also the synergetic efficiency of FMT and the prebiotics on MetS.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Currently, clinical studies evaluate the efficacy of nicotinic acid in combination with statins in reducing relevant clinical endpoints, including progression of cardiovascular disease, the incidence of major cardiovascular events, and associated mortality. It was observed that SNPs in GPR109A determine response to therapy by niacin in the lowering of lipoproteins [ 164 ]. A recent epidemiological analysis of adverse reactions with niacin indicated severe GI symptoms and anxiety.…”
Section: Lipid Metabolitesmentioning
confidence: 99%
“…It also plays a role in T cell proliferation 32 and is an Alzheimer's disease risk gene 33 . HCAR2 (hydroxyl-carboxylic receptor 2) is a niacin receptor gene that mediates niacin decrease of Lipoprotein(a) 34 . Nicotinic acid action on HCAR2 causes atherosclerosis to regress in humans and mice.…”
Section: Lipid Metabolismmentioning
confidence: 99%